Augmenting halal food integrity through supply chain integration - Mohd Helmi Ali,; Zafir Mohd Makhbul,; Kim, Hua Tan; Abdul Hafaz Ngah, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of this paper is to highlight the importance of the supply chain integration in augmenting food integrity from the perspective of the focal companies. A series of case studies in four halal food supply chain (fast food, kopitiam, casual dining, and fresh processed food) in Malaysia were conducted in understanding the companies’ best practices in safeguarding halal food integrity. The findings from the case studies were then suited and discussed in the paradigm of arc of integration theory. The results provide strong empirical evidence on how a stronger supply chain integration could enhance halal food integrity. Theoretically, this paper advances supply chain integration paradigm discussion into food industry. It offers a novel understanding of supply chain integration relevancy in food industry and in particular the supply chain integration strategy in safeguarding halal food integrity. In addition, the paper offers propositions on how halal integrity could be better achieved through a range of integration strategies. In practice, the paper offers a way forward to the managers in selecting the most relevant type of supply chain integration practices.